A comparison of soft‐coded and hard‐coded relaying. Issue 3 (13th August 2012) - Molu, Mehdi M.; Goertz, Norbert
ABSTRACT 'Amplify and forward' and 'decode and forward' are two main relaying functions that have been proposed since the advent of cooperative communications. 'Soft decode and forward' is a recently introduced relaying principle that employs a soft‐input, soft‐output (SISO) Bahl–Cocke–Jelinek–Raviv (BCJR) encoder in the relay; the intention is to combine the benefits of the classical two relaying algorithms. To compare the performance of a SISO BCJR encoder with a conventional hard convolutional encoder, we establish a suitable framework of two cooperative scenarios employing soft and hard coding in the relay. A novel approach, the mutual information loss due to data processing, is proposed for analysis. We also introduce a new approach to estimate the bit error rate and the equivalent channel signal‐to‐noise ratio for the relaying techniques considered in the paper, involving both the hard and soft encoders. The results reveal new aspects of soft/hard encoding, and we discuss the usefulness of SISO BCJR encoding compared with conventional hard encoding. Copyright © 2012 John Wiley & Sons, Ltd.